2012
DOI: 10.2105/ajph.2011.300514
|View full text |Cite
|
Sign up to set email alerts
|

Rapid HIV Testing in Large Urban Jails

Abstract: HIV prevalence is higher in jails than in the community, yet many jails do not conduct HIV testing. Jails in Baltimore, Maryland; Philadelphia, Pennsylvania; and the District of Columbia have implemented innovative rapid HIV testing programs. We have summarized the results of these programs, including the numbers of persons tested, rapid and confirmatory HIV test results, and numbers of persons newly diagnosed with HIV. We have described facilitators and challenges of implementation. These programs confirmed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 11 publications
(8 reference statements)
1
52
0
Order By: Relevance
“…Rapid HIV testing in jails may be used to expedite notification of results to both patient and provider and thus facilitate a more expedited evaluation for ART as well as expedite partner notification and risk reduction. 9,[14][15][16] Evaluation and treatment algorithms that can be implemented following a new HIV diagnosis, or upon knowledge that someone with chronic HIV infection has been incarcerated, must be developed. The removal of structural barriers to the delivery of HIV care will enable more efficient evaluation and consideration for ART initiation prior to jail release.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rapid HIV testing in jails may be used to expedite notification of results to both patient and provider and thus facilitate a more expedited evaluation for ART as well as expedite partner notification and risk reduction. 9,[14][15][16] Evaluation and treatment algorithms that can be implemented following a new HIV diagnosis, or upon knowledge that someone with chronic HIV infection has been incarcerated, must be developed. The removal of structural barriers to the delivery of HIV care will enable more efficient evaluation and consideration for ART initiation prior to jail release.…”
Section: Discussionmentioning
confidence: 99%
“…9 While HIV testing in jails is possible, we do not know whether persons newly diagnosed with HIV infection in jails go on to complete the initial evaluation for HIV and start ART. The short length of stay likely impacts the ability to deliver HIV test results, complete a baseline evaluation [CD4 count, HIV plasma viral load (PVL), and HIV genotype], initiate ART, and provide linkage to community HIV care after release.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In city jails, rapid HIV testing may improve the identification of new cases and subsequent care coordination by shortening the time from test to result, but this approach requires particular attention to setting-specific issues, including space limitations, confidentiality, and detainee turnover for success (10) (103) noted high rates of STIs in young people entering jail and juvenile detention centers and recommended testing for chlamydia and gonorrhea in adolescents and young women and, where local prevalence warrants, in young and adult men. Similarly, syphilis screening was recommended only where local epidemiology suggests heightened risk in the population.…”
Section: Interventions To Improve Health Services Delivered In Jail Amentioning
confidence: 99%
“…For example, since 2008, the Baltimore City jails have offered HIV rapid testing to inmates on a voluntary basis. 55 However, while attention to HIV prevention among incarcerated partners has greatly increased, 56 more work focusing on non-incarcerated partners is needed. The study has shown that incarcerated individuals do not account for the entire link between HIV and incarceration; nonincarcerated partners also may introduce HIV/STIs to the relationship.…”
mentioning
confidence: 99%